“Prisoner’s Bars”, a traditional and popular game in the Spanish physical education (1807-1936) - Brasó Rius, Jordi; Torrebadella Flix, Xavier (Revista Complutense de Educación, 2015)
For a long time, the game of Prisoner’s Bars or Prisoner’s Base has been considered for youth and occidental educators an excellent way of recreation and physical hardening. The main objective of this article is the historical and social analysis of prisoner’s base game. This analysis allows us to obtain a cultural approach of the institutionalization process of physical games in the contemporary school. The context of the study is the civilization and social construction of a bourgeois model of values. The methodology is based on a literature review of primary sources and the hermetic analysis built from other historicist related studies. The acquired results make reference to the Prisoner’s game in Spain since the sixteenth century. It was confirmed its important role in the amount of games played by young people during the nineteenth and the beginning of twentieth century’s. However, it was also used as a recreational-educational game during physical education classes. This use in education entails the apparition of rules avoiding the violent features of the game. Besides, this game was a substitute of football when there was no ball and it was a symbolism of regenerationism and national identity. In conjunction with these characteristics, it also appears its disciplined character, its complexity –higher than in numerous team sports–, its war origins, its use as healthy activity and its mixed gender practice. The main conclusion of this analysis is that Prisoner’s game was the first collaboration-oppositional team game with coeducational use. In addition, it is inferred that its practice decreased due to the English sports importation, which has more detailed rules, especially soccer. Nowadays, the use of Prisoner’s game could improve the competence work; besides it is beneficial to enhance additional abilities related with cognition and motor skills.